2022
DOI: 10.21203/rs.3.rs-1167386/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delirium Risk Factors in Hospitalized Patient: a Comprehensive Evaluation of Underlying Diseases and Medications in Different Wards of a Large Urban Hospital Center in Iran

Abstract: Background: Delirium is a neurobehavioral syndrome, which is characterized by fluctuation of mental status, disorientation, confusion and inappropriate behavior and it is prevalent among hospitalized patients. Recognizing modifiable risk factors of delirium is the key point for improving our preventive strategies and restraining its devastating consequences. The present study investigated a wide range of possible predisposing factors of delirium, mainly focused on underlying diseases and mediations, of hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…This therapeutic class reduces excessive dopaminergic activity, a major contributing factor in delirium, which favors its prescription in critical care situations. 39,40 Studies have shown that delirium affects a significant proportion of older people in ICUs and that haloperidol, the predominant antipsychotic in the study sample, prevents delirium. 39,40 In patients receiving mechanical ventilation, agitation, which often results from delirium, increases the risk of extubation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This therapeutic class reduces excessive dopaminergic activity, a major contributing factor in delirium, which favors its prescription in critical care situations. 39,40 Studies have shown that delirium affects a significant proportion of older people in ICUs and that haloperidol, the predominant antipsychotic in the study sample, prevents delirium. 39,40 In patients receiving mechanical ventilation, agitation, which often results from delirium, increases the risk of extubation.…”
Section: Discussionmentioning
confidence: 97%
“…39,40 Studies have shown that delirium affects a significant proportion of older people in ICUs and that haloperidol, the predominant antipsychotic in the study sample, prevents delirium. 39,40 In patients receiving mechanical ventilation, agitation, which often results from delirium, increases the risk of extubation. Among older adults with nasoenteral tubes, confusion, which is also associated with delirium, can lead to accidental tube removal.…”
Section: Discussionmentioning
confidence: 97%